Enhancing University Students’ Academic Presentation Skills through Mnemonic-Based Strategies - Putra , Octa Pratama; Kayen, Hazrat Shah (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
In university-level education, academic presentations serve as a crucial component in fostering active learning and communication skills. Despite their significance in supporting the teaching and learning process, many students still find it challenging to deliver effective and structured presentations, particularly when required to adhere to academic conventions and clarity of expression. This study aims to explore how mnemonic-based strategies improve students’ academic presentation skills through an in-depth analysis of a specific group of learners. This study employed a qualitative research methodology using a case study approach. The participants in this study consisted of five students from the English Language and Literature Study Program, Faculty of Communication and Business, who were purposefully selected. Based on the five selected students, several problems in delivering academic presentations include: 1) lacking confidence during the presentation; 2) presenting unstructured points; 3) being unable to present without reading from the text; 4) struggling to create effective and engaging PowerPoint slides; and 5) failing to convey the main points clearly. After being introduced to the mnemonic-based strategy, the five students were able to deliver their academic presentations effectively and confidently. The findings indicate that a single keyword was sufficient to trigger recall and effectively support students in delivering their academic presentations.